p(x)=2x^3 + 7x^2 + 2x - 3. (a) Use the factor theorem to prove that x + 3 is a factor of p(x). (b) Simplify the expression (2x^3 + 7x^2 + 2x - 3)/(4x^2-1), x!= +- 0.5

(a) The factor theorem states that: the polynomial f(x) has a factor (x - a) if and only if f(a) = 0.Use that information, we know that (x + 3) is a factor of p(x) if p(-3) = 0. So let's test it:p(-3) = 2(-3)^3 +7(-3)^2 +2(-3) - 3 = 2(-27) + 7(9) -6 -3 = -54 + 63 -9 = 0.(b) Notice here that the numerator is just p(x) and that the denominator is just (2x + 1)(2x - 1).Since we know that (x + 3) is a factor is p(x), we can factorise it out of our polynomial:2x^3 + 7x^2 + 2x - 3 = (x + 3)(2x^2 + x - 1) = (x + 3)(2x - 1)(x + 1)So putting all this information into our expression gives us:(x + 3)(2x - 1)(x + 1)/(2x + 1)(2x - 1) Cancel out the (2x - 1) term.(x + 3)(x + 1)/(2x + 1)

Answered by James M. Maths tutor

9164 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Given an integral of a function parametrized with respect to an integer index n, prove a given recursive identity and use this to evaluate the integral for a specific value of n.


What is a derivative and how are they used?


Differentiate the function f(x)=2xsin3x


I struggle with modelling with differential equation, is there an easier way of interpreting this type of wordy question?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences